THE POLITICAL SPIRITUALITY OF TUAN GURU BATAK SABBAN RAJAGUKGUK: MODERATING SOCIAL AND POLITICAL COHESION IN NORTH SUMATRA - Rakhmat Syawal; Hasan Bakti Nasution; Mardian Idris Harahap (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research analyzes the spiritual-political perspectives and contributions of Tuan Guru Batak (TGB) Syekh Ahmad Sabban Rajagukguk amidst the challenges of polarization and the politicization of religion in North Sumatra. As a Sufi scholar and intellectual figure, TGB offers a model that bridges spirituality with the realities of practical politics. Employing a qualitative method with a case study approach, data were collected through in-depth interviews, observation, and documentary studies. Thematic analysis was utilized to identify and elaborate on the meanings derived from the data. The findings indicate that TGB’s spirituality is neither apolitical nor escapist; rather, it serves as an ethical and practical foundation for socio-political engagement. He views politics as an instrument for da’wah (Islamic propagation) aimed at realizing the common good (kemaslahatan), not merely as an arena for power struggles. TGB’s contributions are multidimensional: intellectually, he emerges as a scholar-academic who integrates tradition with modern science; socio-politically, he acts as a moral actor and mediator who safeguards social cohesion; and in terms of leadership, he bequeaths an inclusive and transformative neo-Sufi model. By rejecting identity politics and promoting Sufistic moderation, TGB demonstrates that spirituality can be a crucial counterbalancing force in preserving diversity and strengthening the foundations of democracy. This model offers relevant inspiration for religious leadership in the contemporary era.